Perceived Stress and Coping Strategies Among Undergraduate Health Science Students of Jimma University Amid the COVID-19 Outbreak: Online Cross-Sectional Survey - Awoke, Mengist; Mamo, Girma; Abdu, Samuel; Terefe, Behailu (Frontiers in Psychology, 2021)
Background: The rapid spread of COVID-19 infection has led countries across the globe to take various measures to contain the outbreak, including the closure of universities. This forced university students to stay home creating enormous stress and uncertainty in their daily life. Objective: This study aimed to assess the perceived stress and coping strategies among undergraduate health science students of Jimma University amid the COVID-19 outbreak. Materials and methods: An online cross-sectional survey was conducted involving 337 undergraduate health science students from August to September 5, 2020. Perceived stress scale (PSS)-10 and Brief-COPE scale were used to assess the level of stress and coping strategies, respectively. Statistical Package for Social Science (SPSS) Version 22 was employed for data analysis. Logistic regression was conducted to identify predictors of high perceived stress. Results: The overall mean (±Standard Deviation (SD)) age of the participants was 22.88 (±1.78) years. The mean (±SD) PSS score was 22.16 (±1.41), and high perceived stress was reported in 121(35.9%) participants. The overall mean (±SD) coping score was 72.34 (±12.31), and approach coping was the predominantly used strategy for coping with stress. Personal perception of being stressed by the daily number of COVID-19 cases/deaths in Ethiopia (AOR=4.61, p<0.01), rare online talk/chat with friends (AOR=4.07, p=0.01), presence of confusion due to the inconsistent strategies developed by the health/Government authorities in view of the scientific recommendations (AOR=2.22, p=0.01), perception of self/family members being at risk of getting sick (AOR=0.53, p=0.03), decreased in household income following COVID-19 pandemic (AOR=3.92, p=0.01), practicing denial (AOR=1.34, p<0.01), self-blame [AOR=1.23, p=0.02), planning (AOR=1.28, p=0.01), and religion (AOR=1.41, p<0.01) means of coping stress were associated with high perceived stress. Conclusion: Over one-third of the participants had a high level of perceived stress, and the majority of them were practicing the effective means of coping with stress. The authors recommend the hosting university in collaboration with the concerned bodies has to develop innovative strategies to improve the psychological well-being of the student.